HUBUNGAN GOVERNMENT SIZE DENGAN KESEJAHTERAAN DI INDONESIA: Peran Moderasi Bonus Demografi - Reny Maselati Margaretha; Khoirunurrofik (Journal Publicuho, 2024)
People's welfare is one of the important goals in the RPJMN 2020-2045 and the Golden Indonesia Vision 2045. One of the government’s roles in realizing welfare is through fiscal policy in the form of government spending, which is assessed by the ratio of government spending to GDP or government size. This study aims to determine the relationship between government size and welfare, especially the role of demographic dividend in moderating the relationship between government size and welfare using panel data of 34 provinces in Indonesia in 2012-2021 and the Fixed Effect Model (FEM). The results show that an increase in government size reduces GRDP per capita, but the existence of a demographic dividend through a low dependency ratio is able to reduce the negative relationship of non-optimal government spending on GRDP per capita. As for poverty, government size is able to reduce poverty, but the presence of the demographic dividend has not been able to play a role in increasing government spending that is more efficient and targeted for the purpose of poverty alleviation. Furthermore, the diversity of regression results obtained based on Indonesia's sub-regions indicates that there are still inequalities in budget planning, the quantity and quality of human resources especially productive age population, and the availability of jobs.